Work-related support needs of registered nurses in a neonatal intensive care unit in the Tshwane District - Funzani Nefale; Nombulelo V. Sepeng; Roinah Ngunyulu (AOSIS, 2023)
Background: Registered nurses in neonatal intensive care units (NICU) are working under stressful environment caused by the need and commitment to provide care for the critically ill neonates. Therefore, there is an imperative need to know and understand the work-related support strategies that can be adapted for registered nurses working in a NICU in the Tshwane District to enable them to provide quality care for the admitted neonates. Aim: To explore and describe the work-related support needs of registered nurses working in a specific NICU situated in the Tshwane District. Setting: The study was conducted in a selected NICU in Tshwane District. Method: A qualitative, exploratory, descriptive, and contextual design was used in this study. In-depth unstructured individual face-to-face interviews were conducted with nine registered nurses working at the selected NICU of an academic hospital. Thematic data analysis was conducted. Results: Three themes, namely teamwork between registered nurses and doctors, staff development in the form of peer seminars, workshops and in-service training, and availability of adequate resources within the workplace arose. Conclusion: This study revealed that the registered nurses working in the NICU in the Tshwane District are in need of work-related support, as it will improve their well-being. Contribution: The contribution of this study will be used by the hospital management to plan strategies that can be adapted for the betterment of the work environment for registered nurses in the NICU and the hospital in general.